Foaming technology using gas counter pressure to improve the flexibility of foams by using high amounts of CO2 as a blowing agent. (15th January 2015) - Hopmann, Christian; Latz, Simon
Abstract: Existing technologies for polyurethane (PU) foaming in discontinuous moulding processes show several disadvantages regarding the achievable foam properties like a limited flexibility of lightweight flexible foams. In contrast, the use of carbon dioxide (CO2 ) as a physical blowing agent offers advantages regarding its inert properties. But up to now, it was not possible to use CO2 for lightweight foams, because high amounts of CO2 lead to an uncontrolled foaming process. Therefore, a new physical foaming technology for moulded PU foam has been developed at IKV in order to enable high amounts of CO2 (up to 10 wt.-%) as a blowing agent. A gas counter pressure inside the mould cavity enables the precise control of the physical foaming process. For this reason, the mould technology as well as the high-pressure metering machine were adapted for the processing of highly loaded reaction mixtures with solved CO2 . Using the new foaming technology, a density of 116 kg/m³ was achieved for rigid foams. In case of flexible foams, it was possible to reduce the density to 61 kg/m³. In comparison to conventional foaming using water as a blowing agent, the compressive strength is reduced to less than 30%, enabling the production of "softer" foams. At the same time, a high quality of the form filling behaviour, competitive to conventional foaming methods, was proven in test series with flow obstacles. Conclusively, the new foaming technology offers a new degree of freedom in adjusting the hardness of lightweight flexible foams and shows a high potential as substitution of physical blowing agents in order to reduce ecological concerns for the foaming of polyurethanes. Graphical abstract: Highlights: A new physical foaming technology for moulded PU foam has been developed. Gas counter pressure enables the use of high amounts of CO2 as a blowing agent. In case of rigid foams, a density of 116 kg/m³ was achieved, exclusively with CO2 . For flexible foams, the density was reduced to a minimum of 61 kg/m 3 . In comparison to chemical foaming the compression strength is reduced to a quarter.